Qualitative Validation of a Novel VR Program for Irritable Bowel Syndrome: A VR1 Study. (8th March 2022) - Spiegel, Brennan M.R.; Liran, Omer; Gale, Rebecca; Khalil, Carine; Makaroff, Katherine; Chernoff, Robert; Raber, Tiffany; Chang, Bianca; Pichetshote, Nipaporn; Rezaie, Ali
Abstract : INTRODUCTION: Although gut-directed psychotherapies are effective for irritable bowel syndrome (IBS), they are rarely prescribed, given a paucity of trained clinicians. Virtual reality (VR) offers a solution by allowing patients to self-practice these techniques in a standardized manner. METHODS: A multidisciplinary team developed IBS/VR, a program that transports users into immersive VR worlds that teach patients about the brain-gut axis, cognitive behavioral therapy, and gut-directed meditation. We tested IBS/VR in Rome IV IBS patients and used inductive analysis to evaluate perceptions and identify recommendations. RESULTS: We achieved thematic saturation after 9 interviews; 3 additional interviews revealed no emergent themes. After making 23 software changes based on patient feedback, we conducted 3 additional interviews which confirmed thematic saturation (N = 15 total). DISCUSSION: This study offers initial validation of the first VR program designed for IBS.